2014
DOI: 10.3389/fnint.2014.00063
|View full text |Cite
|
Sign up to set email alerts
|

What visual illusions teach us about schizophrenia

Abstract: Illusion, namely a mismatch between the objective and perceived properties of an object present in the environment, is a common feature of visual perception, both in normal and pathological conditions. This makes illusion a valuable tool with which to explore normal perception and its impairments. Although still debated, the hypothesis of a modified, and typically diminished, susceptibility to illusions in schizophrenia patients is supported by a growing number of studies. The current paper aimed to review how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 87 publications
9
115
0
6
Order By: Relevance
“…Moreover, consistent with our prior study in chronic patients (Argyelan et al, 2014) we also observed significant abnormalities in first-episode patients compared with healthy volunteers in sensory networks (both visual, auditory, and somatosensory). This may be particularly noteworthy because both prior empirical and theoretical work implicate a disruption in perceptual processes in schizophrenia (Butler et al, 2001;Grillon et al, 1992;Javitt et al, 1996;Notredame et al, 2014;Patterson et al, 2008;Umbricht and Krljes, 2005). Consistent with the global connectivity analysis, we identified lower expression scores in first-episode patients overall compared with healthy volunteers using ICA.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, consistent with our prior study in chronic patients (Argyelan et al, 2014) we also observed significant abnormalities in first-episode patients compared with healthy volunteers in sensory networks (both visual, auditory, and somatosensory). This may be particularly noteworthy because both prior empirical and theoretical work implicate a disruption in perceptual processes in schizophrenia (Butler et al, 2001;Grillon et al, 1992;Javitt et al, 1996;Notredame et al, 2014;Patterson et al, 2008;Umbricht and Krljes, 2005). Consistent with the global connectivity analysis, we identified lower expression scores in first-episode patients overall compared with healthy volunteers using ICA.…”
Section: Discussionsupporting
confidence: 74%
“…We argue that mid-level perceptual features may be strongly influenced by top down expectations so that only a subset of detectors must be active at a time. This is consistent with a hypothesis introduced by Notredame et al that explains how visual illusions could be caused by prior expectations overtaking the actual stimulus [18]. A lot of research in computer vision has also been done on building models that perform top down inference [26] [25].…”
Section: Top Down Inferencesupporting
confidence: 67%
“…Two separate fMRI and EEG studies examined potential mechanisms for this phenomenon: applying structurally analogous DCMs to fMRI and EEG data, these two studies consistently found a strengthening of bottom-up connections and diminished top-down connectivity in patients, consistent with the notion of reduced precision of predictions about facial stimuli (Dima et al, 2009(Dima et al, , 2010. Notably, weakening of top-down predictions may explain a range of perceptual alterations in schizophrenia (Notredame et al, 2014) and may also play a role in the initial formation of delusions (Schmack et al, 2013).…”
Section: Application To Clinical Questionsmentioning
confidence: 55%